A History of Agriculture and Prices in England, Volume 7 Part 1, 1703–1793 From the Year after the Oxford Parliament (1259) to the Commencement of the Continental War (1793) - Rogers, James E. Thorold (Cambridge library collection. British and Irish History, General, 1902)
Since early times, agriculture has been pivotal to England's economy. This is the seventh in a magisterial seven-volume, eight-piece compilation by the economist James E. Thorold Rogers (1823–90), which represents the most complete record of produce costs in England between the thirteenth and eighteenth centuries. Drawing on a variety of sources including college archives and the Public Record Office, Rogers documents the fluctuating prices of commodities such as livestock, wheat, hay, wool, textiles and labour in a time of great economic change, when the growing economy of the early middle ages was shaken by famine and the Black Death, and then gradually recovered towards the Agrarian Revolution. First published in 1902 (completed and edited by Rogers' son), this two-part volume presents in Part 1 data from 1703 to 1793, showing the prices of a range of products; Part 2 consists of further documents collected by Rogers for the work